(untitled) (Research, Society and Development, 2021)
Plant growth regulators, which can alter the plant size and anatomy, allow the use of cultivars of interest that do not have a modern leaf architecture, making higher plant densities possible. The objective of this study was to evaluate the agronomic performance of second season corn, grown at different plant densities and under Trinexapac-ethyl applications at different stages of crop development. The field study was carried out in two growing seasons (2013 and 2014), at the Fazenda Escola of the State University of Londrina. Fifteen treatments were evaluated in a randomized block, 5 x 3 factorial design, at five plant densities (40,000, 60,000, 80,000, 100,000 and 120,000 plants per hectare), of Trinexapac-ethyl applied in three stages: control (no application), V6 and V9, with four replications. The morphological plant characteristics, the yield components and grain yield were evaluated. Increases in plant density raise the plant height, reduce the number of grains per ear, ear length and 100-kernel weight, and have no influence on grain yield. The application of Trinexapac-ethyl in stage V9 reduces plant and ear insertion height and 100-kernel weight.